2017
DOI: 10.15761/imm.1000298
|View full text |Cite
|
Sign up to set email alerts
|

A novel Ubc9 -dependent pathway regulates SIRT1- ER-α Axis and BRCA1- associated TNBC lung metastasis

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous disease and has a higher rate of recurrence and distant metastasis. African-American (AA) women have a higher frequency of BRCA1 mutations and TNBC compared to other populations. Basal-like tumors have a higher rate of brain, lung and distant nodal metastasis more than other TNBC subtypes, contributing to higher mortality rate. Our previous work suggested Ubc9, a SUMO E2-conjugating enzyme to induce proliferation and migration of BRCA1-incompetent TNBC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…Similarly, our results suggest association of high UBC9 expression with poor prognosis in PAAD as well as differential levels (low in normal samples) of promoter methylation concerning lymph node metastasis. The role of UBC9 in PAAD in our study is consistent with that reported in other studies across diverse tumor types, including lung, colorectal, prostate, ovarian, and breast cancers as well as melanoma [ 36 41 ]. In addition, we determined the diagnostic potential of UBE2I in PAAD and COAD, which has rarely been reported in cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, our results suggest association of high UBC9 expression with poor prognosis in PAAD as well as differential levels (low in normal samples) of promoter methylation concerning lymph node metastasis. The role of UBC9 in PAAD in our study is consistent with that reported in other studies across diverse tumor types, including lung, colorectal, prostate, ovarian, and breast cancers as well as melanoma [ 36 41 ]. In addition, we determined the diagnostic potential of UBE2I in PAAD and COAD, which has rarely been reported in cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in BRCA1 lead to dysregulation of the Ubc9/caveolin-l/vascular endothelial growth factor (VEGF)/SIRTl/oestrogen receptor (ER)-α axis, promote EMT and trigger the migration of HCC1937 triple-negative breast cancer cells in vitro. 58 , 59 The STAG2 gene, the protein product of which regulates centromere cohesion, is often mutated in various cancers. Most STAG2 mutations are truncating and, as shown in the U2OS osteosarcoma cell line, the loss of this gene leads to increased EMT-associated tumour cell migration in vitro, coincident with decreased expression of E-cadherin and increased expression of N-cadherin.…”
Section: Gene Alterationsmentioning
confidence: 99%
“…In our previous work, we first proposed a novel Ubc9 -Caveolin-1-VEGF-SIRT1-ER-a axis that is facilitated by functional BRCA1 [19]. When BRCA1 is mutated, this axis is disturbed, and it results in TNBC with epithelial to mesenchymal transition that allows for metastasis to the lungs [20]. This mechanism identifies a novel downstream target for BRCA1: SUMO conjugating enzyme Ubc9.…”
Section: Brca1 Ubc9 Sirtuins and A Potential Axis For Novel Therapymentioning
confidence: 99%
“…BRCA1 tethers Ubc9 to prevent Ubc9 tumorpromoting effects. Furthermore, when Ubc9 is bound to BRCA1, SIRT1 expression is activated [20]. Mutant BRCA1 cannot bind Ubc9 leading to accumulation of the enzyme causing reduced expression of Caveolin-1 and increased levels of vascular endothelial growth factor (VEGF), which promotes tumor growth and metastasis.…”
Section: Brca1 Ubc9 Sirtuins and A Potential Axis For Novel Therapymentioning
confidence: 99%